Optimization and Regression Analysis of Friction Stir Processing Parameters of AA5083/Coal Composites for Marine Applications - Oritonda Muribwathoho; Velaphi Msomi; Sipokazi Mabuwa (Crystals)
This study aimed to optimize friction stir processing parameters to enhance the mechanical properties of AA 5083/coal composites, a novel material combination with potential applications in marine environments. By systematically varying process parameters such as tilt angle, traverse speed, and rotational speed using a Taguchi experimental design, the FSP process was optimized. Signal-to-noise ratio and analysis of variance techniques were used to determine the most influential parameters on microhardness and ultimate tensile strength. A regression model was developed to predict composite behavior under these optimal conditions. This study found that a combination of 900 rpm, 60 mm/min, and a 2° tilt angle significantly improved mechanical properties. This research contributes to the advancement of FSP for producing high-performance, lightweight, and corrosion-resistant aluminum composites, particularly for marine applications.